Measuring the Effectiveness of the Indigenous-Based Experiential Learning Model on Pre-service Science Teachers' Creative Thinking Skills - Widyastuti, Fatma; Sajidan; Saputro, Sulistyo; Sutikno; Fadloli; Probosari, Riezky Maya (Universitas Negeri Semarang, 2026)
Indigenous-based Experiential Learning (IbEL) model has been developed to promote pre-service science teachers' creative thinking skills. This model emphasizes a more holistic, community-based education grounded in Indigenous knowledge and cultural practices. This study aims to evaluate the effectiveness of the IbEL model in enhancing the pre-service science teachers' creative thinking skills. The study involved 29 participants who were randomly selected from a larger population. The participants were assessed using a pretest and posttest design to determine the changes in their creative thinking skills after being taught using the IbEL model. The study utilized a standardized evaluation instrument to measure creative thinking skills, including Fluency, Flexibility, Originality, Elaboration, Risk-Taking, Complexity, Curiosity, and Imagination. The data analysis method used was Rasch analysis with stacking and racking techniques. Using pretest and posttest evaluations, the researchers found a significant increase in creative thinking skills, with the Observation course showing a higher increase. The study highlights the importance of creativity in teaching and learning and how enhancing creative thinking skills can improve student achievement. The IbEL model encourages students to appreciate local knowledge and experience, context, and situation in learning, and direct experience, leading to more culturally sensitive research outcomes. The study contributes to the development of better learning models to enhance pre-service science teachers' creative thinking skills.